Design and rationale of the Edoxaban Treatment in routiNe clinical prActice for patients with Atrial Fibrillation in Europe (ETNA-AF-Europe) study. Issue 2 (February 2019) - De Caterina, Raffaele; Kelly, Peter; Monteiro, Pedro; Deharo, Jean Claude; de Asmundis, Carlo; López-de-Sá, Esteban; Weiss, Thomas W.; Waltenberger, Johannes; Steffel, Jan; de Groot, Joris R.; Levy, Pierre; Bakhai, Ameet; et al.
Abstract : Aim: Edoxaban, a nonvitamin K antagonist oral anticoagulant, is an oral factor Xa inhibitor approved for the prevention of stroke and systemic embolism in adult patients with atrial fibrillation and for the treatment and secondary prevention in adult patients with venous thromboembolism (VTE). This study details the design of the Edoxaban Treatment in routiNe clinical prActice for patients with Atrial Fibrillation in Europe (ETNA-AF-Europe) study – a postauthorization observational study, which is part of the postapproval plan for edoxaban agreed with the European Medicines Agency. Methods: The ETNA-AF-Europe study (Clinicaltrials.gov: NCT02944019) is a multicenter, prospective, observational study that enrolled 13 980 patients with atrial fibrillation treated with edoxaban from 852 sites across 10 European countries (Austria, Belgium, Germany, Ireland, Italy, the Netherlands, Portugal, Spain, Switzerland, and the United Kingdom). Patients treated with edoxaban were prospectively enrolled and will be followed up for 4 years with yearly follow-up visits. Assessments: The primary objective of the ETNA-AF-Europe study is to assess the real-world safety of edoxaban by evaluating bleeding events, including intracranial hemorrhage; drug-related adverse events, such as hepatic events; and cardiovascular and all-cause mortality. In addition, efficacy will be assessed by recording major adverse cardiovascular events including stroke, systemic embolic events, transient ischemic attacks, and also VTE episodes, acute coronary syndromes, and hospitalizations related to cardiovascular condition. Event rates will be compared with event rates reported in the PREvention oF thromboembolic events-European Registry in Atrial Fibrillation in atrial fibrillation (PREFER in AF) and PREFER in AF Prolongation registries, and in the Effective Anticoagulation with Factor Xa Next Generation in Atrial Fibrillation – Thrombolysis in Myocardial Infarction 48 study datasets. Abstract : Supplemental Digital Content is available in the text